Differential expression of Wnts after spinal cord contusion injury in adult rats. - Carmen María Fernández-Martos (Public Library of Science (PLoS), 2011)
Background Spinal cord injury is a major cause of disability that has no clinically accepted treatment. Functional decline following spinal cord injury is caused by mechanical damage, secondary cell death, reactive gliosis and a poor regenerative capacity of damaged axons. Wnt proteins are a family of secreted glycoproteins that play key roles in different developmental processes although little is known of the expression patterns and functions of Wnts in the adult central nervous system in normal or diseased states. Findings Using qRT-PCR analysis, we demonstrate that mRNA encoding most Wnt ligands and soluble inhibitors are constitutively expressed in the healthy adult spinal cord. Strikingly, contusion spinal cord injury induced a time-dependent increase in Wnt mRNA expression from 6 hours until 28 days post-injury, and a narrow peak in the expression of soluble Wnt inhibitors between 1 and 3 days post-injury. These results are consistent with the increase in the migration shift, from day 1 to 7, of the intracellular Wnt signalling component, Dishevelled-3. Moreover, after an initial decrease by 1 day, we also found an increase in phosphorylation of the Wnt co-receptor, low-density lipoprotein receptor-related protein 6, and an increase in active β-catenin protein, both of which suffer a dramatic change, from a homogeneous expression pattern in the grey matter to a disorganized injury-induced pattern. Conclusions Our results suggest a role for Wnts in spinal cord homeostasis and injury. We demonstrate that after injury Wnt signalling is activated via the Wnt/β-catenin and possibly other pathways. These findings provide an important foundation to further address the function of individual Wnt proteins in vivo and the pathophysiology of spinal cord injury.